The impact of legal framework on cyberfraud perpetration in the South African banking industry - Akinbowale, Oluwatoyin Esther; Zerihun, Mulatu Fekadu; Mashigo, Polly (International Journal of Management and Sustainability, 2025)
This study examines the impact of legal framework on cyberfraud perpetration in the South African banking industry. The banking institution in South Africa is faced with the increasing rate of cyberfraud perpetration, which affects the performance of the banks, customer satisfaction, profitability, as well as banking reputation. This study combines the explanatory research approach, systematic literature review, and quantitative survey to investigate the impact of legal framework on cyberfraud perpetration in the South African banking industry. Initially, a total of 1579 literature were gathered from institution’s report and academic database using search engines. However, the application of the inclusion criteria screened the literature to 50. Furthermore, a quantitative survey involving the use of a structured questionnaire and expert sampling of key organisational staff saddled with the responsibility of cyberfraud mitigation was conducted across the 17 licensed banks in South Africa, and the outcome was analysed in the Statistical Package for Social Sciences (SPSS) 2022 environment. The outcome of the review indicated the presence of legal frameworks, yet with an increasing rate of cyberfraud perpetration. Both the outcome of the review and survey criticised the non-stringent nature of the cyber laws and the non-implementation of some of its provisions.